Sharing in the company : determinants, processes and outcomes of employee participation - Kato, Takao, active 2017; Poutsma, Erik,; Ligthart, Paul E. M., (Advances in the economic analysis of participatory and labor-managed firms ;, 2017)
This volume gathers recent insights into the determinants, developments and outcomes of employee share ownership. It focuses on a number of new emerging themes in the literature and tests some of the relationships using several, notable European datasets. The authors discuss employee share ownership from the perspective of strategic human resource management (SHRM) and present the 'contextual SHRM model,' where employee ownership is influenced by several environmental pressures, which indicated the need for five specific 'fits' of employee ownership. These fits are: fit of employee ownership with strategy of the firm, with the organizational cultural heritage, with the wider social cultural environment; fit with other HRM practices (internal fit); fit with personal characteristics of employees. The authors explore these fits with several new emerging theories and demonstrate what firms that want employee ownership to be an effective HRM policy need to do.